2009
DOI: 10.1557/jmr.2009.0348
|View full text |Cite
|
Sign up to set email alerts
|

Formation and bioactivation of Zr-Al-Co bulk metallic glasses

Abstract: A Cu-and Ni-free Zr-based metallic glass with high glass-forming ability was found in the Zr-Al-Co ternary system. The eutectic Zr 56 Al 16 Co 28 alloy could be cast into glassy cylindrical rods with diameters up to 18 mm. The glassy alloy exhibited high tensile fracture strength of 1830 MPa and low Young's modulus of 83 GPa in conjunction with better corrosion resistance compared with the glassy Zr 57 Nb 5 Al 10 Ni 12.6 Cu 15.4 in a simulated body fluid. Hydrothermal-electrochemical treatment in the aqueous 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(39 citation statements)
references
References 22 publications
3
36
0
Order By: Relevance
“…Wada et al [13] 28 , the alloys that melted and solidified with the similar phases were confirmed by crystallization process, which is consistent with the reported ternary equilibrium phase diagram [14]. Figure 5 shows the XRD patterns of Zr 56 Al 16 Co 28 amorphous alloy after heating to 900 K with a heating rate of 20 K/min; no Zr-Al-Co phase was found, which was probably because the amount was so small.…”
Section: Calculation Calculation Modelsupporting
confidence: 80%
“…Wada et al [13] 28 , the alloys that melted and solidified with the similar phases were confirmed by crystallization process, which is consistent with the reported ternary equilibrium phase diagram [14]. Figure 5 shows the XRD patterns of Zr 56 Al 16 Co 28 amorphous alloy after heating to 900 K with a heating rate of 20 K/min; no Zr-Al-Co phase was found, which was probably because the amount was so small.…”
Section: Calculation Calculation Modelsupporting
confidence: 80%
“…By the absence of Ni, Cu, Be, as harmful element, Zr-Al-Co BMGs became the promising system for biomaterial. Co is classified as toxic element, but the total mass of Co ions released from glassy state after implantation is lower than that on Co-alloy [6].…”
Section: Introductionmentioning
confidence: 98%
“…However, Zr-Co-Al BMGs suffer on limited plastic strain and restrict their applications [6]. Introducing certain amount of crystalline phases inside the glassy matrix is reported could modify their mechanical properties [7], where, in optimum and homogeneous crystalline content, their limited plastic strain could be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…A number of Zr-based BMGs such as Zr-Al-NiCu, 1) Zr-Ti-Cu-Ni-Be, 2) Zr-Cu-Fe-Al, 3) Zr-Cu-Ni-Al-Ti, 4) and Zr-Al-Co 5) have been developed and reported in the literature. These Zr-based BMGs exhibit a series of superior properties, including high strength, high hardness, relatively low Young's modulus, large elastic limit and near-net-shape formability, compared to ordinary crystalline alloys.…”
Section: Introductionmentioning
confidence: 99%